Independent Curriculum and Strengthening Pancasila Identity in the Young Generation: Kurikulum Merdeka dan Penguatan Identitas Pancasila pada Generasi Muda - Dwi, Sintia; Hasanah, Uswatun (Gerasi Insan Nusantara, 2024)
The Merdeka Curriculum, as a new educational paradigm, introduces a holistic approach that emphasizes character development, moral values, and leadership skills. This research aims to describe the impact of the Merdeka Curriculum in helping the character and leadership of the younger generation in Indonesia. The method used in this research is library research. In the context of implementation, this paradigm has succeeded in creating students who not only excel academically, but also have integrity, empathy, and readiness to lead. The importance of national identity, patriotism and environmental sustainability is reflected in the emphasis of the Merdeka Curriculum. The history of the nation, Pancasila values and Indonesian culture are an integral part of the curriculum, creating graduates who have a strong national identity. Continuous character development, leadership skills, and orientation to lifelong learning are the hallmarks of the Merdeka Curriculum. Collaboration with parents, the community and related institutions strengthens the educational ecosystem, creating an environment that supports the development of student character. The emphasis on critical, creative and global skills as well as religious values and spirituality makes the Merdeka Curriculum the foundation of comprehensive education. In this way, the Merdeka Curriculum has proven itself to be an educational model that is successful in forming the character and leadership of the younger generation. The results of this research provide insight into how this paradigm can continue to improve the quality of education, producing future leaders who are competitive and responsible.